1953
DOI: 10.1021/ac60081a012
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Coulometric Titration with Photometric Detection of Equivalence

Abstract: To eliminate the troubles associated with anomalous behavior of sensing electrodes and to reduce the number of electrodes in a titration vessel have been dual purposes of a successful attempt to develop apparatus and procedures for automatic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1953
1953
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Another example of a specific analytical method is the analysis of carbon. The carbon content of the deposits has been determined by combustion, converting it to CO 2 , which could be measured by coulometric titration [93].…”
Section: Chemical Analysismentioning
confidence: 99%
“…Another example of a specific analytical method is the analysis of carbon. The carbon content of the deposits has been determined by combustion, converting it to CO 2 , which could be measured by coulometric titration [93].…”
Section: Chemical Analysismentioning
confidence: 99%
“…Coulometry and Related Topics.-Coulometric titrations have been reviewed critically and c o m p r e h e n s i ~e l y . ~~~ A simple gas coulometer 379 and apparatus for automatic coulometric titration 380 381 have been described. Because of the increased use of coulometric titrations, the coulomb has been suggested as the primary standard in all titrimetric processes in preference to any chemical standard.382 I t has been shown that it is possible to deduce correctly from polarographic investigations the conditions required for obtaining optimum yields of coulometric reagent~3~3 Coulometric titrations and back-titrations where oxidants and reductants are alternately generated have been successfully carried out .…”
Section: Instrumental Methodsmentioning
confidence: 99%
“…They can be performed at small concentrations where the inflection of a potentiometric end point would be very small, and in solutions of high ionic strength, where conductometric methods are inadequate. They are a distinct advantage in coulometric titrations, because there can be no interference between generation and detection systems (3,10). And, because many chemical systems are adaptable to a color change at the end point, they have wide applicability.…”
Section: Literature Citedmentioning
confidence: 99%
“…Although there has been considerable work in recent years in this field (3,4,6,(9)(10)(11), the first was done some 30 years ago by Muller and Partridge (7). The principles are still the same, but a different approach using new techniques and new components has led to the development of a useful commercial device.…”
Section: Literature Citedmentioning
confidence: 99%